Severe bronchiolitis before and after the COVID-19 pandemic: a retrospective database analysis by the Italian Network of PICU study group (TIPNet) - Francesca Izzo; Rosanna I. Comoretto; Angela Amigoni; Marco Daverio; Elena Zoia; Veronica Diotto; Francesco Sacco; Claudio Nettuno; Anna Tessari; Enzo Picconi; Maria Cristina Mondardini; Gaia Milvia Bregant; et al. (Journal of Anesthesia, Analgesia and Critical Care)
Abstract Background The first post-COVID-19 pandemic year demonstrated an unusual bronchiolitis epidemic in both hemispheres and has been attributed to the removal of barriers implemented during SARS-CoV-2 infection. Several countries reported an increase in respiratory syncytial virus (RSV) bronchiolitis, with more hospitalizations and a greater need for respiratory support. We aimed to evaluate the consequences of the COVID-19 pandemic on the epidemiology and management of severe bronchiolitis in pediatric intensive care units (PICUs) in Italy. Methods Multicenter, retrospective, cohort database analysis. All children younger than 24 months admitted to 7 PICUs from October 2017 to April 2023 diagnosed with bronchiolitis were included. We compared patients from pre-COVID and post-COVID eras, excluding patients from the 2020–2021 season due to low numbers. Logistic regression models were used to assess the impact of the pre-/post-COVID period on the need for invasive ventilation. Results Seven hundred fifteen patients were admitted to PICU during the study period, 451 patients pre-COVID and 251 patients post-COVID. Patients in the post-COVID group were older, had more comorbidities, and had higher Pediatric Index of Mortality scores at admission but the need for respiratory support was not significantly different. There was high variability in bronchiolitis management across centers. Presenting pre-COVID was protective against the risk of mechanical ventilation, adjusted for age and disease severity at admission (OR 0.38, 95% CI 0.16–0.89), while RSV infection increased the risk of intubation (OR 2.49, 95% CI 1.1–5.63). Conclusions PICUs have faced an unexpected peak of significantly more severe cases of bronchiolitis after the COVID-19 pandemic, which did not require increased respiratory support.